Questioning authority: the theology and practice of authority in the Episcopal Church and Anglican Communion - Wondra, Ellen K. (Studies in episcopal and Anglican theology, 2018)
Communion challenged -- Impaired communion -- The highest degree of communion possible -- Questioning authority -- Power, responsibility, and authority -- Differentiated authority -- Relational theology -- Catholicity and conciliarity -- Conclusions and prospects